The Effect of Hyperoxia on Central and Peripheral Factors of Arm Flexor Muscles Fatigue Following Maximal Ergometer Rowing in Men - Volianitis, Stefanos; Rasmussen, Peter; Petersen, Nicolas C.; Secher, Niels H. (Frontiers in Physiology, 2022)
Purpose: This study evaluates the effect of hyperoxia on cerebral oxygenation and neuromuscular fatigue mechanisms of the elbow flexor muscles following ergometer rowing. Methods: In eleven competitive male rowers (age, 30 ± 4 yrs.), we measured near-infrared spectroscopy determined frontal lobe oxygenation (ScO2) and trans-cranial Doppler ultrasound determined middle cerebral artery mean flow velocity (MCA Vmean) combined with maximal voluntary force (MVC), peak resting twitch force (Ptw) and cortical voluntary activation (VATMS) of the elbow flexor muscles using electrical motor point and magnetic motor cortex stimulation, respectively, before, during and immediately after 2000 m all-out effort on rowing ergometer with normoxia and hyperoxia (30% O2). Results: Arterial haemoglobin O2 saturation was reduced to 92.5 ± 0.2% during exercise with normoxia but maintained at 98.9 ± 0.2% with hyperoxia. The MCA Vmean increased by 38% (P < 0.05) with hyperoxia, while only marginally increased with normoxia. Similarly, ScO2 was not affected with hyperoxia but decreased by 7.0 ± 4.8% from rest (P = 0.04) with normoxia. The MVC and Ptw were reduced (7 ± 3% and 31 ± 9%, respectively, P = 0.014), while VATMS was not affected by the rowing effort in normoxia. With hyperoxia, the deficit in MVC and Ptw was attenuated, while VATMS was unchanged. Conclusion: These data indicate that even though hyperoxia restores frontal lobe oxygenation the resultant attenuation of arm muscle fatigue following maximal rowing is peripherally rather than centrally mediated.